La représentation graphique de voies paysagères, médium d’évolution infrastructurelle - Manon Espinasse (Projets de Paysage)
Representing a territory makes it possible to understand it to decide what changes to make (Corboz, 1983); representing the road infrastructure allows for a concrete understanding of its contribution to the environment it traverses (compositional elements, topographic positioning, etc.). Rendering such concrete elements is necessary to support transformations, or “transitions” even (Birch 2016; Barles, 2018). Little research has been done on graphic representations of road infrastructures, however, among these is “America’s National Park Roads and Parkways: Drawings from the Historic American Engineering Record” (Davis et al., 2004) which presents 331 hand-drawn plans including section and axonometric drawings of parkways and park roads. These drawings come from a compilation describing twelve landscape routes which was created by pluri-disciplinary departments from the American National Parks (engineers and landscape architects) between 1988 and 2002. Examination of this record shows the part played by graphic representation as a multiform medium in the process of development and transformation (Söderström, 2000) and which helps to enlighten, generate knowledge, build a multidisciplinary perspective, create a common language, and support action and new practices.